Determination of Mycotoxin Contamination Levels in Rice and Dietary Exposure Assessment - Jose Troestch; Stephany Reyes; Aracelly Vega (Journal of Toxicology)
The contamination by aflatoxins, ochratoxin A, and zearalenone of samples of paddy and polished rice stored in silos located in Chiriquí, Panama, was evaluated. A total of 23 samples were extracted using immunoaffinity columns and analyzed by high-performance liquid chromatography (HPLC) with a fluorescence detector (FLD) and post-column photochemical derivatization. For the method used, the detection limits were lower than 0.25 μg/Kg for aflatoxins (AFB1, AFB2, AFG1, AFG2) and ochratoxin A and 9.35 μg/Kg for zearalenone; the limits of quantification were between 0.25 and 18.75 μg/Kg, respectively. Of the samples analyzed, all of the paddy rice samples were positive for at least one of the mycotoxins studied, zearalenone being the one found with the highest incidence (90.91%); for the polished rice samples, the mycotoxin with the highest incidence was zearalenone (50%), although in concentrations lower than those established in European legislation (100 μg/Kg). The estimate of the daily zearalenone intake according to the concentrations found was always less than 0.07 μg/Kg/bw. This is the first report on the determination of 6 mycotoxins in rice grains from Panama by the HPLC-FLD methodology. Considering the high incidence of mycotoxins in the analyzed rice samples, regular control in the production process is recommended to improve quality and ascertain its safety.